Tell our story : multiplying voices in the news media - Reid, Julie; McKinley, Dale T. (Wits University Press, 2020)
Investigating bias in the mainstream media, the authors dismiss the idea that some groups are voiceless, arguing that they are being deliberately ignored. Adopting an audience-centred approach and research in practice in three South African communities, they draw out a set of practical guidelines for journalists on listening journalism.